One Experience, Three Expressions: A Multidimensional Analysis of Employee Engagement - Natalya, Lina; Sin, Gabrielle Sinata; Putra, Devin Sandy (Journal of Educational, Health and Community Psychology, 2025)
This study aims to analyze employee engagement from a multidimensional perspective by differentiating three forms of employee engagement expression: Convey (speaking positively about the organization), Commit (desire to stay), and Contribute (effort to provide maximum contribution). The data were collected from 1,235 employees across various sectors in Indonesia through the Employee Experience Survey (EES) developed by KTM Consulting, using a population study. The research population comes from various industry sectors and job backgrounds, ranging from staff to managerial levels, thus adequately reflecting the diversity of organizational contexts in Indonesia. This study employed independent sample t-tests to examine differences in engagement scores across demographic groups and multiple linear regression analysis to identify the contribution of each cluster to engagement expressions, using a significance level of p ≤ 0.05. The results indicate that each form of engagement is influenced by different driving factors: Brand & Reputation has a significant impact on Convey (45.15%), Career Development & Growth Opportunities primarily influences Commit (21.58%), and Purpose & Meaning serves as the main driver for Contribute (30.84%). These findings underscore that a one-dimensional approach to measuring engagement risks overlooking the psychological dynamics underlying the employee-organization relationship. By understanding engagement expressions separately, organizations can design more precise, relevant, and long-term interventions to enhance work motivation, retention, and employee contribution.